Does Otosclerosis Affect Dark and Transitional Cells in the Human Vestibular Labyrinth?. Issue 2 (February 2017) - Kaya, Serdar; Paparella, Michael M.; Cureoglu, Sebahattin
Abstract : Hypothesis: The density of vestibular dark cells (DCs) and vestibular transitional cells (TCs) can be quantitatively decreased in human temporal bones with otosclerosis. Background: Previous reports have shown that otosclerosis can lead to vestibular symptoms. Methods: We examined 61 human temporal bone specimens from 52 deceased donors with otosclerosis group–with and without endosteal involvement (EI), and with and without endolymphatic hydrops (EH)–versus 25 specimens from 18 age-matched controls. Using light microscopy, we evaluated the nonsensory epithelium of the lateral semicircular canal (LSC) and posterior semicircular canal (PSC) of the human vestibular labyrinth, focusing on the density of DCs and TCs. Results: In both the LSC and the PSC, as compared with the control group, the mean density of DCs significantly decreased in the EI ( + ) group, in the EI (+) and EH (+) subgroup, and in the EI (+) and EH (−) subgroup ( p  < 0.05). In addition, we found a significant difference in the mean density of DCs between the EI (+) group and the EI (−) group in the LSC and in the PSC ( p  < 0.05). But we found no significant difference in the mean density of TCs in any of the otosclerosis groups or subgroups as compared with the control group ( p  > 0.05). Conclusion: We found a decrease in the density of DCs associated with EI in human temporal bone specimens with otosclerosis, regardless of the presence of EH. This decrease might cause damage in ion and water transportation, leading to vestibular symptoms.